Two subject specific modelling approaches to construct base-age invariant polymorphic site index curves with varying asymptotes - Sprengel, Lars; Spiecker, Heinrich; Wu, Shuirong (Silva fennica (Helsinki, Finland : 1967), 2022)
For constructing growth and yield models the concept of site index as measure of productivity is crucial. Here, we use nonlinear mixed-effects models (NLME) with random individual effects and nonlinear models with dummy variables as fixed individual effects (NLFE) to fit mechanistic growth functions to stem analysis data of the economically most important tree species in Zhongtiaoshan forest region, China. The Richards and Lundqvist function are formulated into five dynamic equations (R1, R2, L1, L2 and L3) applying the generalized algebraic difference approach (GADA), which inherit polymorphism, varying asymptotes and base-age invariance. According to Akaike information criterion the R1 model as NLFE fits height growth data of CarriÃ¨re, Franch., Koidz., Blume and Sukaczev best, while for Blume R2 as NLFE fits height growth data best. For Mayr L1 as NLME has been selected as best model, as R1 and R2 both as NLFE and NLME are not extrapolating the comparably short length of height growth data well enough. However, according to the root mean square error and bias differences between model fits of both the selected equation and the chosen model fitting approach are not so clear. Presented families of height growth curves serve as planning tools to identify site index and therefore assess productivity of forest stands in the studied region. A direct comparison of the productivity of forest stands of the same tree species is possible due to base-age invariance of the selected models. Pinus tabuliformis Pinus armandii Quercus liaotungensis Quercus aliena Betula platyphylla Quercus variabilis Larix principis-rupprechtii